The Nexus Among Transformational Leadership and Firm Performance: Testing the Mediating Role of Knowledge Sharing (American Journal of Applied Statistics and Economics, 2023)
The purpose of this paper is to clarify the mediating roles of active and passive knowledge sharing (KS) in the relationship between transformational leadership (TL) and specific aspects of firm performance namely operational and financial performance. The paper used Analysis of Moment Structures (AMOS) and Structural Equation Modelling (SEM) to investigate the influence of TL and knowledge sharing (KS) on aspects of firm performance using data from a survey of 235 manufacturers and suppliers in Vietnam. The empirical findings show the significant and positive influence of TL, and KS activities in supply chain networks on firm performance. It highlighted the key role of active and passive KS in linking the effect of TL on firm’s operational and financial performance. Especially, this study reveals that TL has a greater effect on financial performance compared to its effects on operational performance. Especially, active KS has a greater effect on both firm’s operational and financial performance compared to the influence of passive KS. The paper has extended the theory of leadership, knowledge management and organizational performance by clarifying the critical roles of TL practice and processes of KS in the supply chain in improving firm’s operational and financial performance.